Penerapan Terapi Genggam Bola Karet Terhadap Kekuatan Otot Pada Pasien Stroke Dibangsal Anyelir Rumah Sakit Umum Daerah (RSUD) dr. Soediran Mangun Sumarso Wonogiri - Frisca Indah Yuliyani; Sri Hartutik; Agus Sutarto (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Background : The number of elderly in RSUD dr. Soediran Mangun Soemarso in April there were 48 people, while in the Anyelir ward itself there were 37 people. Over time, complaints that appear in elderly people who have had a stroke are sudden facial weakness, sudden feeling of confusion, difficulty speaking, nausea, sudden vomiting and numbness or tingling. Objective : To find out the results of implementing rubber ball handheld therapy on muscle strength in stroke patients. Method : This type of research uses a descriptive method with a case study approach. Findings: The muscle scale before hand-held rubber ball therapy in stroke patients was 3, and the muscle scale after hand-held therapy in stroke patients was 4. Implication There are differences in development before and after being given hand-held rubber-ball therapy in the elderly who have had a stroke, namely experienced an increase in motor muscle strength in elderly patients.